Features of Regulation of Urban Planning Activities in the Federal Territory “Sirius” - V. A. Mayboroda (Теоретическая и прикладная юриспруденция)
The article deals with the legislatively fixed features of the regulation of urban development in the new public-law formation in the Russian Federation — the federal territory “Sirius”. The method used in fixing these features does not meet the goals of creating the federal territory “Sirius” and will not allow to realize the powers of the public authorities of the federal territory, since it violates causality in the system of regulatory regulation and does not imply a legal shift in the balance of interests.